2020
DOI: 10.21608/mnj.2020.149901
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Program for Mothers to Improve the Quality of Life of Their Children With Congenital Heart Disease

Abstract: Background: Congenital heart defects (CHD) is one of the major congenital irregularities among children, representing as a major worldwide wellbeing issue. Aim:this study aimed toexamine a guiding program for mothers to improve the quality of life of their children with congenital heart disease. Design: A quasi-experimental design was used. Setting: The study was carried out at the Cardiology Department and Outpatient Clinic of Mansoura University Children Hospital (MUCH). Subjects: A convenient sample of 70 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…The current study revealed that it was found that more than two thirds of mothers in the study group were housewives. The same result was found by [18] they studied 70 mothers and their children with CHD and found that the majority of the mothers in the study group were housewives. As regards mothers' consanguineous, more than half of studied sample had consanguineous marriages.…”
Section: Discussionsupporting
confidence: 82%
“…The current study revealed that it was found that more than two thirds of mothers in the study group were housewives. The same result was found by [18] they studied 70 mothers and their children with CHD and found that the majority of the mothers in the study group were housewives. As regards mothers' consanguineous, more than half of studied sample had consanguineous marriages.…”
Section: Discussionsupporting
confidence: 82%